Predicting Advertising Pulsing Policies in an Oligopoly: A Model and Empirical Test - Villas-Boas, J. Miguel (Marketing Science, 1993)
Given that firms pulse in advertising, should firms pulse in or out of phase? It is shown that out of phase maximizes the oligopoly profits and is also the Markov perfect equilibrium of the infinite horizon game. The basic intuition for this result comes from the following fact: it is more profitable to increase consideration when the competitor's consideration is lower. Evidence from several product categories seems to support this theoretical result.
https://katalog.adlr.link/Record/ai-55-aHR0cHM6Ly93d3cuanN0b3Iub3JnL3N0YWJsZS8xODM3Mzk